Greek Fire, Poison Arrows, and Scorpion Bombs: How Tumor Cells Defend Against the Siege Weapons of Cytotoxic T Lymphocytes - McKenzie, Brienne; Khazen, Roxana; Valitutti, Salvatore (Frontiers in Immunology, 2022)
CD8+ cytotoxic T lymphocytes (CTLs) are the main cellular effectors of the adaptive immune response against cancer cells, which in turn have evolved sophisticated cellular defense mechanisms to withstand CTL attack. Herein we provide a critical review of the pertinent literature on early and late attack/defense events taking place at the CTL/target cell lytic synapse. We examine the earliest steps of CTL-mediated cytotoxicity (“the poison arrows”) elicited within seconds of CTL/target cell encounter, which face commensurately rapid synaptic repair mechanisms on the tumor cell side, providing the first formidable barrier to CTL attack. We examine how breach of this first defensive barrier unleashes the inextinguishable “Greek fire” in the form of granzymes whose broad cytotoxic potential is linked to activation of cell death executioners, injury of vital organelles, and destruction of intracellular homeostasis. Herein tumor cells deploy slower but no less sophisticated defensive mechanisms in the form of enhanced autophagy, increased reparative capacity, and dysregulation of cell death pathways. We discuss how the newly discovered supra-molecular attack particles (SMAPs, the “scorpion bombs”), seek to overcome the robust defensive mechanisms that confer tumor cell resistance. Finally, we discuss the implications of the aforementioned attack/defense mechanisms on the induction of regulated cell death (RCD), and how different contemporary RCD modalities (including apoptosis, pyroptosis, and ferroptosis) may have profound implications for immunotherapy. Thus, we propose that understanding and targeting multiple steps of the attack/defense process will be instrumental to enhance the efficacy of CTL anti-tumor activity and meet the outstanding challenges in clinical immunotherapy.